Biomarkers in Hepatobiliary Cancers: What Is Useful in Clinical Practice? - Boilève, Alice (Cancers (Basel), 2021)
SIMPLE SUMMARY: In oncology, a new era has emerged in the last ten years with the development of targeted and immune therapies. In hepatocellular carcinoma (HCC), several targeted agents (sorafenib, lenvatinib, cabozantinib, regorafenib, and ramucirumab) are approved and immunotherapy is now validated in combination with bevacizumab, while theragnostic biomarkers are lacking for patient selection. Conversely, in biliary tract cancer (BTC), immune therapies are still investigational while targeted therapies are now crucial considering the complex molecular landscape of BTC. In this review, we provide an overview of (i) the main prognostic biomarkers in HCC and BTC, (ii) the main theragnostic biomarkers in both tumors, and lastly (iii) what is recommended in clinical practice. ABSTRACT: Hepatocellular carcinoma (HCC) and biliary tract cancers (BTC) exhibit a poor prognosis with 5-year overall survival rates around 15%, all stages combined. Most of these primary liver malignancies are metastatic at diagnostic, with only limited therapeutic options, relying mainly on systemic therapies. Treatment modalities are different yet partially overlapping between HCC and BTC. The complex molecular profile of BTC yields to several actionable therapeutic targets, contrary to HCC that remains the field of antiangiogenic drugs in non-molecularly selected patients. Immunotherapy is now validated in the first line in HCC in combination with bevacizumab, while clinical activity of single agent immunotherapy appears limited to a subset of patients in BTC, still poorly characterized, and combinations are currently under investigation. In this review, we provide a critical evaluation and grading of clinical relevance on (i) the main prognostic biomarkers in HCC and BTC, (ii) the main theragnostic biomarkers in both tumors, and lastly (iii) what is recommended in clinical practice.